AJARAN NEO-SUFISME KH. ABDUL HANNAN MA’SUM (STUDI DI PESANTREN FATHUL ‘ULUM KWAGEAN) - Moch. Azis Qoharuddin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
This study aims to construct and describe the neo-Sufism teachings of KH. Abdul Hannan Ma’sum at the Fathul ‘Ulum Islamic Boarding School in Kwagean, Kediri Regency. Neo-Sufism, as proposed by Fazlur Rahman, is a renewed form of Sufism that not only emphasizes individual spirituality but also encourages social activism and positive engagement in worldly life. This research employs a qualitative approach using phenomenological-hermeneutic methods, along with data collection techniques such as in-depth interviews, participatory observation, and document studies. The findings reveal that KH. Abdul Hannan Ma’sum’s neo-Sufism teachings are manifested through three main methods: bandongan (collective study, particularly of the Ihya’ ‘Ulum al-Din), exemplary behavior and advice (mau’izah), and the granting of spiritual practices (ijazah amaliyah) to students. The core values imparted include a strong enthusiasm for learning and seeking knowledge, hard work and spiritual striving (mujahadah), patience and perseverance (istiqamah), strengthening of liturgical recitations and remembrance (wirid and dhikr), economic self-sufficiency, a life of asceticism despite abundance, as well as social concern and generosity. These teachings shape a contextual pesantren-based Sufism that responds to contemporary challenges without abandoning the roots of classical Islamic scholarship. Thus, KH. Abdul Hannan Ma’sum successfully actualized the principles of neo-Sufism within the educational system and social praxis of the pesantren. His teachings not only form the spiritual character of the students but also encourage their active and meaningful participation in social life.